Go duck hunting! - Simons, Lisa M. B., 1969- (Capstone Press, 2021)
"A duck hunter crouches in a camouflage tent called a blind. Suddenly, a flock of ducks takes flight from the water. The hunter has one chance to take the shot! Readers will learn about the gear, weapons and skills they need to enjoy this exciting outdoor sport"--
Includes bibliographical references and index.
Ages 8-11
Grades 4-6
Keywords: Duck shooting -- Juvenile literature